Standar Pelayanan Keperawatan Pada Penilaian Akreditasi Rumah Sakit Versi 2012 Di Rumah Sakit “X” Tahun 2016 - Ni Nyoman Dwi Sutrisnawati; Dumilah Ayuningtyas (CV. Multi Kreasi Media, 2023)
Hospitals are required to carry out accreditation periodically, at least once every three years. The development of hospital accreditation standards in Indonesia has undergone adjustments in 2016 referring to the 2012 version of accreditation standards which focus on patients. Hospital